2019
DOI: 10.1080/17461391.2019.1660726
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of acute exercise intensity on memory and BDNF isoform concentrations

Abstract: Little is known about the biological mechanisms underlying the beneficial effect of acute exercise on memory or the influence of single nucleotide polymorphisms (SNPs) on this effect. Brain-derived neurotrophic factor (BDNF) is a putative biological mechanism, and while findings from human studies are equivocal, they have neglected to assess how exercise affects individual BDNF isoform (proBDNF, mBDNF) concentrations in serum or the influence of the BDNF val66met SNP on BDNF isoform concentrations. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
1
16
1
5
Order By: Relevance
“…Regarding specifically acute exercise responses, concentrations of mBDNF increased immediately after acute exercise, in agreement with previous results from other studies with different populations 30 32 . We did not observe any difference between acute responses to HIIT and MICT, unlike the study by Piepmeier et al 15 , in which they found increases of this neurotrophin only in vigorous intensity. Our results indicate EE/session might be an important variable rather than intensity per se.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Regarding specifically acute exercise responses, concentrations of mBDNF increased immediately after acute exercise, in agreement with previous results from other studies with different populations 30 32 . We did not observe any difference between acute responses to HIIT and MICT, unlike the study by Piepmeier et al 15 , in which they found increases of this neurotrophin only in vigorous intensity. Our results indicate EE/session might be an important variable rather than intensity per se.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding BDNF isoforms, the concentrations of proBDNF in the present study did not change acutely nor after 6 weeks, as in agreement with the study of Piepmeier et al 15 , while mBDNF increased in both experimental acute exercise sessions, independent of group. These results are relevant because they show the concentration of proBDNF did not change in the same way of mBDNF after a single bout of exercise or short-term training.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Even though there are many interactions taking place, exercise has been shown to be the catalyst in BDNF affecting the brain [9]. Indeed, acute exercise is recognized to promote the release of serum BNDF [51] and this release seems to be dependent on exercise intensity [52,53]. For example, Winter and colleagues [54] tested the effect of acute exercise on BDNF serum levels and learning using both HIIT, MICE, and rest interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It would be worthwhile for future research to evaluate whether there are individual participant differences that influence the effects of acute exercise on memory (Crush & Loprinzi, 2017;Sibley & Beilock, 2007). For example, brain-derived neurotrophic factor (BDNF) met carrier status may moderate the effects of acute exercise on memory (Piepmeier et al, 2019). In addition, although our set of experiments implemented sample sizes that are at or above the median sample size among studies on this topic (see Figure 9 in Pontifex et al, 2019), future studies that evaluate individual differences may require larger sample sizes.…”
mentioning
confidence: 99%